Analisis Tingkat Kesulitan Siswa Dalam Menulis Cerita Pada Mata Pelajaran Bahasa Indonesia di Kelas IV UPTD SPF SDN 61 Kampung Baru - Wilda Handayani; A Rahman Rahim; Abdul Rajab (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to analyze students' difficulties in writing stories in Indonesian language subjects in Class IV UPTD SPF SDN 61 Kampung Baru. The subjects in this research were 19 students of UPTD SPF SDN 61 Kampung Baru consisting of three students with high abilities, three students with medium abilities, and three students with low abilities. Data collection was carried out using written tests and continued with individual interviews to obtain valid data. The results of the analysis of the difficulty test for writing stories for students showed an average score of 67.63 for students. From these data it can be seen that the ability of class IV students in writing stories is still quite low. Of the 3 questions asked, many students still had difficulty answering questions related to structure and choosing words. Based on the results of interviews with 9 students, it is known that the difficulties experienced by students in the high subject category are that students have difficulty determining titles and connecting words to make a complete sentence. The difficulties experienced by moderate subjects were difficulty putting together good and interesting sentences in determining the content of the story and the noisy classroom atmosphere affecting their concentration in writing. Meanwhile, the difficulties experienced by low subjects are that they are not interested in writing a story so it is difficult to write, they have difficulty deciding what words to use, and they have no interest in writing long texts so they prefer not to do it. Based on the results of the research that has been carried out, it can be concluded that the level of difficulty for students in writing stories in Indonesian language subjects is still quite low.